Determining High Conservation Values in Production Landscapes: Biodiversity and Assessment Approaches - Styring, Alison R.; Unggang, Joanes; Ragai, Roslina; Kueffner, Kayleigh; Froehlich, Daniel; Megom, Nyegang; Joseph, Li; Jukie, Alex; Tarang, Moses; Nazrin, Mohamad; Sulok, Kiding; Sekina, Kinsy; et al. (Frontiers in Environmental Science, 2022)
Conversion of natural, heterogenous tropical forests to intensively managed, monoculture- production landscapes is a major threat to biodiversity. This phenomenon is driven by global demand for commodities such as wood, palm oil, sugar, and soybean. The economies of many countries in tropical areas depend on these commodities, but there is a need to ensure economic welfare while protecting biodiversity. Certification schemes such as those developed by the Forest Stewardship Council and Roundtable for Sustainable Palm Oil are intended to provide incentive to companies to employ environmentally and socially sustainable production practices. One element of these certification schemes is the concept of High Conservation Values (HCVs) which fall into six categories that encompass ecological indicators and human dimensions. The HCV process has expanded beyond production landscapes to include long-term conservation planning. Despite expansion, implementation of the HCV process as it pertains to biodiversity is challenged, in part, by a lack of specificity regarding target metrics. Another challenge is that, in practice, there is a short time period for assessment, resulting in limited collection of primary data and a reliance on secondary data sources for interpolation. HCV guidance advances a precautionary approach to assessment, but in some regions, there is not enough known about the biology, behavior, or interspecific associations of species to effectively assess what is not observed. In this paper, we assess environmental HCVs in a well-studied timber production system in Sarawak, East Malaysia. Using an original long-term multi-method dataset of avifaunal surveys as well as published datasets of other taxa, we (1) assess biodiversity metrics at the site including presence of Rare, Threatened, and Endemic species, (2) assess change over time at assessment locations, and (3) evaluate costs and benefits of the various methods and provide best practice recommendations for HCV assessment and long-term monitoring. Finally, we recommend transparent data-archiving and sharing for improved accuracy and efficiency in the HCV process. Managed landscapes are important areas for ecological research that are beneficial not only to the restoration and conservation of species and ecosystems but also to well-informed certification and long-term sustainability.